Analisis Konten Film “Mak Cepluk” Sebagai Pelestarian Permainan Tradisional Indonesia - Safitri, Tsania Firda Ayu; Kurniawan, Fajar Adhi (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2023)
Children's interest in using modern games is very strong, making children less interested in traditional games. The way that can be done to preserve traditional games is to socialize traditional games. One of the effective socialization today is to disseminate it using communication media, namely films. The method used in this research is to use qualitative research methods. The results showed that the content of the movie "Mak Cepluk" contains cultural preservation content, especially in the game of pletokan. The two elements that make up the movie are narrative and cinematic elements, the narrative elements in the movie "Mak Cepluk" contain a coherent story and contain elements of traditional games clearly. From the cinematic elements, the efforts to preserve the traditional game of pletokan are well depicted from shooting techniques, composition, editing techniques, and movie continuity.